Parasites in a man-made landscape: contrasting patterns of trematode flow in a fishpond area in Central Europe - Soldánová, M; Faltýnková, A; Scholz, T; Kostadinova, A (Parasitology, 2011)
We have explored a large body of novel data focusing on small-scale temporal and spatial patterns in the composition and structure of larval trematode communities in Lymnaea stagnalis (L.) from a typical Central European agricultural landscape. The 5 eutrophic fishponds studied provide excellent environments for the development of species-rich and abundant trematode communities. Nine prevalent species were consistently present in component communities, but had differential contribution to the parasite flow in the 5 ponds resulting in significant contrasting patterns of community similarity and the prevalence of the 3 major transmission guilds driving this similarity. Component communities split into 2 groups: (i) those from the large pond dominated by anatid and larid generalists with active miracidial transmission; and (ii) those from the smaller ponds dominated by 2 plagiorchioideans infecting snails via egg ingestion. We put forward 3 hypotheses for the remarkable differences in larval trematode flow in the similar and closely located eutrophic ponds: (i) species-specific differences in parasite colonization potential displayed by an 'active-passive' dichotomy in miracidial transmission strategies of the species; (ii) top-down effects of pond context on transmission pathways of the trematodes; and (iii) competition as an important mechanism in eutrophic environments with a bottom-up effect on component community structure.
Keywords: Animals; Trematoda; biodiverzita; Seasons; Ponds; Host-Parasite Interactions; interakce hostitele a parazita; roční období; stadia vývoje; Czech Republic; rybníky; Biodiversity; ekosystém; Česká republika; Ecosystem; Snails; Life Cycle Stages; zvířata; hlemýždi